Capitalizing on the (false) consensus effect: two tractable methods to elicit private information [dataset] - Schmidt, Robert J. (Universität, 2019)
We propose and experimentally test two tractable methods to incentivize the elicitation of private information: Benchmark and Coordination. Both me...